The influence of the addition of red pepper (Capsicum annuum L.) and red amaranth (Alternanthera amoena Voss) on the feed for color acumen of the guppies fish (Poecilia reticulata) - Hipit Putri Apriasih; Ana Sofia; Latif Dwi Cahyo; Salsabila Nurdini Sakinah; Zenobia Anisa; Eric Armando; Tholibah Mujtahidah; Ayuningtyas Ayuningtyas (Airlangga University, 2021)
Guppy fish is currently in high demand because they has interesting color variations such as red, blue, yellow. The carotenoid content in red peppers and red spinach is able to increase the brightness of the color of the fish. This research aims to find out the effect of the addition of red peppers and red spinach on guppy fish color. Completely Randomized Design with 3 treatment and 3 repetitions was used. The research data was analyzed by using the Adope Photoshop app by observing the discoloration that occurred before and after the treatment by using color libraries. The study found that the percentage of blue and purple in guppy fish increased. This was related to the absence of carotene that associated with protein and produces carotenoproteins. The most prominent discoloration result was the treatment 1 (addition of peppers). In treatment 1 there was a significant discoloration of the blue color with the code 732-0 from 0% to 11.9%, while in the treatment 2 (addition of spinach) color coded 732-0 was changed from 0% to 5.88%, the treatment 3(control) treatment was changed from 1.21 % to 0.6%. Meanwhile, the purple color with the code 728-0 on treatment 1 from 0% to 2.36%, on treatment 2 from 0% to 0.22% and on treatment 3 purple color did not came out. It can be concluded that the most influential to the color of guppy fish was peppers, spinach and control treatment, respectively. Keywords : red spinach, carotene, guppy fish, red peppers, color.